Answer:
ok first you do the small one. 13 * 5 * 1/2 = 32.5 then you do 35 *1/2=17.5. you then divide 32.5/17.5=1.86
Step-by-step explanation:
Answer:
9
Step-by-step explanation:
we know by definition that
![f^{-1}(f(x))=x\\\\f^{-1}(\frac{2x}{3})=x\\\\f^{-1}(x)=ax\\\\f^{-1}(\frac{2x}{3})=a(\frac{2x}{3})=x\\\\f^{-1}(x)=\frac{3x}{2}](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28f%28x%29%29%3Dx%5C%5C%5C%5Cf%5E%7B-1%7D%28%5Cfrac%7B2x%7D%7B3%7D%29%3Dx%5C%5C%5C%5Cf%5E%7B-1%7D%28x%29%3Dax%5C%5C%5C%5Cf%5E%7B-1%7D%28%5Cfrac%7B2x%7D%7B3%7D%29%3Da%28%5Cfrac%7B2x%7D%7B3%7D%29%3Dx%5C%5C%5C%5Cf%5E%7B-1%7D%28x%29%3D%5Cfrac%7B3x%7D%7B2%7D)
so now we evaluate
![f^{-1}(6)=\frac{3*6}{2}\\\\=3*3\\\\f^{-1}(6)=9](https://tex.z-dn.net/?f=f%5E%7B-1%7D%286%29%3D%5Cfrac%7B3%2A6%7D%7B2%7D%5C%5C%5C%5C%3D3%2A3%5C%5C%5C%5Cf%5E%7B-1%7D%286%29%3D9)
and if we want to do an extra step
![f^{-1}(f(6))=6\\\\f^{-1}(\frac{2*6}{3})=f^{-1}(4)=\frac{3*4}{2}=6](https://tex.z-dn.net/?f=f%5E%7B-1%7D%28f%286%29%29%3D6%5C%5C%5C%5Cf%5E%7B-1%7D%28%5Cfrac%7B2%2A6%7D%7B3%7D%29%3Df%5E%7B-1%7D%284%29%3D%5Cfrac%7B3%2A4%7D%7B2%7D%3D6)
which works.
Answer:
10 points
Step-by-step explanation:
per 2 days you lose 5 points. To get to 4 days you multiply 2 by 2 and get 4 and 5 by 2 and get 10. So per 4 days he loses 10 points.
3 x 8 = 24
3 x -2 = -6
reply if you this was wrong or you needed a different answer pls >:(
Answer:
-5/24
Step-by-step explanation:
You first change -7/12 to -14/24, and 3/8 to 9/24 so they have the same denominator. You then do -14/24 + 9/24. That will be the same as the opposite of the answer to 14/24 - 9/24.
14/24 - 9/24 = 5/24
-5/24